2017
DOI: 10.1016/j.tate.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of teaching practices and reading skills at the first and third grade in Finland and Estonia

Abstract: The Early Childhood Classroom Observation Measure was used to observe 91 first-grade and 70 third-grade teachers in Estonia and Finland. Using a person-oriented approach, four profiles of teaching practices were identified in grade 1: the child-centred style, teacherdirected style, child-dominated style and a mixture of the child-centred and teacher-directed styles. An additional profile, the extreme-child-centred style, was found in grade 3. Children taught by child-centred teachers showed the highest reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 27 publications
3
33
1
Order By: Relevance
“…Although it has been argued that teachers focus more on the nature of classroom activities that engage students to enact a reasoning process and high‐order thinking rather than on either teacher‐oriented and/or student‐oriented instructions (Boston & Smith, ), three broad concepts are widely used to describe teaching practice. They include the teacher‐centred approach, student‐centred approach, and ‘student–teacher interaction’ approach (Cuban, ; Kember, ; Kikas, Silinskas, Jogi, & Soodla, ; Tang et al ., ). Comparatively, teacher‐centred approaches focus more on the content, the time, and the conditions of teaching.…”
Section: Introductionmentioning
confidence: 97%
“…Although it has been argued that teachers focus more on the nature of classroom activities that engage students to enact a reasoning process and high‐order thinking rather than on either teacher‐oriented and/or student‐oriented instructions (Boston & Smith, ), three broad concepts are widely used to describe teaching practice. They include the teacher‐centred approach, student‐centred approach, and ‘student–teacher interaction’ approach (Cuban, ; Kember, ; Kikas, Silinskas, Jogi, & Soodla, ; Tang et al ., ). Comparatively, teacher‐centred approaches focus more on the content, the time, and the conditions of teaching.…”
Section: Introductionmentioning
confidence: 97%
“…In Finland, child-centered practices, modification of instruction according to the students' skills, and individualized support for learning are highly valued and evident in teaching practices (Kiuru et al 2015;Nurmi et al 2013). Meanwhile, a variety of child-rearing values (Tulviste and Kikas 2010) and practices (Palu and Kikas 2007;Tang et al 2017) are found among Estonian teachers. For example, alongside with child-centered and combined child-centered and teacher-directed, remarkable amount of Estonian elementary school teachers (but only a few Finnish teachers) use predominantly child-dominated practices in classroom (Tang et al 2017).…”
Section: Educational Systems and Reading Instruction In Estonia And Fmentioning
confidence: 99%
“…Meanwhile, a variety of child-rearing values (Tulviste and Kikas 2010) and practices (Palu and Kikas 2007;Tang et al 2017) are found among Estonian teachers. For example, alongside with child-centered and combined child-centered and teacher-directed, remarkable amount of Estonian elementary school teachers (but only a few Finnish teachers) use predominantly child-dominated practices in classroom (Tang et al 2017).…”
Section: Educational Systems and Reading Instruction In Estonia And Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the need for reading skills in Higher Education is much different than in Middle School. (Sidek, 2014; (Goux, Gurgand, & Maurin, 2017;Tang et al, 2017) on the other hand, reading skills is also the most frequently used skill in students' academic life.…”
Section: Introductionmentioning
confidence: 99%